2017
DOI: 10.1371/journal.pone.0180012
|View full text |Cite|
|
Sign up to set email alerts
|

Exploitation rates of two benthic resources across management regimes in central Chile: Evidence of illegal fishing in artisanal fisheries operating in open access areas

Abstract: There is an urgent need to quantify the impacts of artisanal fisheries and define management practices that allow for the recovery and conservation of exploited stocks. The extent of illegal catch is particularly critical as a driver of overexploitation in artisanal fisheries. However, the lack of data at proper spatial scales limits the evaluation of illegal fishing and effectiveness of management practices. We used a catch curve analysis to estimate total instantaneous mortality as a proxy of fishing pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 51 publications
(108 reference statements)
3
21
1
Order By: Relevance
“…This finding suggests that OAAs, whose total area is more than 50 times larger than grounds currently managed as TURFs, may be substantially degraded and overfished. Several authors have suggested that resources in OAAs might be heavily exploited and even depleted (González et al 2006, Andreu-Cazenave et al 2017, de Juan et al 2017, Oyanedel et al 2017. Interestingly, our results do not show significant temporal declines in OAA CPUAs, suggesting either shifts in effort over time or that OAAs were depleted prior to 2000.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…This finding suggests that OAAs, whose total area is more than 50 times larger than grounds currently managed as TURFs, may be substantially degraded and overfished. Several authors have suggested that resources in OAAs might be heavily exploited and even depleted (González et al 2006, Andreu-Cazenave et al 2017, de Juan et al 2017, Oyanedel et al 2017. Interestingly, our results do not show significant temporal declines in OAA CPUAs, suggesting either shifts in effort over time or that OAAs were depleted prior to 2000.…”
contrasting
confidence: 54%
“…Assessments are typically conducted by private environmental consultants, whose fees have increased in part because of the relatively small number of such companies available in Chile (Gelcich et al 2009, Davis et al 2015. Additionally, extensive illegal fishing (González et al 2006, Andreu-Cazenave et al 2017, Oyanedel et al 2017 suggests that local fishing organizations must dedicate significant time and resources to enforcement in TURFs. Though the Chilean government recognizes that there is poaching activity and, in theory, is responsible for apprehending and penalizing poachers, in practice the responsibility of detecting poaching in TURFs often falls on fishing organizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One can thus wonder whether the concomitant regional changes in habitats (ocean sprawl, e.g. Aguilera 2018) and fisheries (Andreu-Cazenave et al 2017) may interact and to which extent it might decrease the biotic resistance herein reported -hypothesis that could be addressed through further experimental and modelling approaches.…”
Section: Consumptive Biotic Resistance Might Vary According To Predatmentioning
confidence: 99%
“…In Brazil, there were more than 970 thousand fishermen in 2014, of which approximately 957 thousand were artisanal fishermen [2], characterized by fishing autonomously, preserving socio-cultural traditions, with family regime, as a source of income, through their own production or in partnership, in small vessels with little autonomy [3, 4]. This type of activity has great socioeconomic importance for several countries such as China, India, Indonesia, Japan and Chile [5, 6], as it represents employment and food security [3, 69].…”
Section: Introductionmentioning
confidence: 99%